2022
DOI: 10.1186/s12910-022-00824-6
|View full text |Cite
|
Sign up to set email alerts
|

Perception and reaction of Nanyang Technological University (NTU) researchers to different forms of research integrity education modality

Abstract: Background Research and academic institutions use various delivery channels to deliver Research Integrity (RI) education in their communities. Yet there is no consensus on the best delivery method and the effectiveness of these channels in inculcating a positive RI culture varies across institutions. Hence, this study aimed to understand the preferences of the research community in Nanyang Technological University (NTU), Singapore. Methods An onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…Various studies have been published on training and education in research integrity, but recent findings confirm this is currently sub-optimal (Bain et al, 2022;Bairi et al, 2022;Chua et al, 2022;Han et al, 2023;Schroter et al, 2018), and our own experience confirms this. Misconduct like citation malpractice can also arise due to coercion by peer reviewers or editors (Fong et al, 2023), which highlights the importance of including publishing ethics training for all stakeholders.…”
Section: Training and Education -Establishing A Feedback Loop And Int...supporting
confidence: 79%
“…Various studies have been published on training and education in research integrity, but recent findings confirm this is currently sub-optimal (Bain et al, 2022;Bairi et al, 2022;Chua et al, 2022;Han et al, 2023;Schroter et al, 2018), and our own experience confirms this. Misconduct like citation malpractice can also arise due to coercion by peer reviewers or editors (Fong et al, 2023), which highlights the importance of including publishing ethics training for all stakeholders.…”
Section: Training and Education -Establishing A Feedback Loop And Int...supporting
confidence: 79%
“…During 2022, (Tomić et al, 2022) did a study in which they made known the existence of approaches to ethics and integrity training in research, one based on the teaching of norms and another based on virtue. In addition, studies were found highlighting respondents' favorable perception of IR education, different preferences on teaching modes, and integrity problem resolutions (Chua et al, 2022;Evans et al, 2022;Felt & Frantz, 2022;Tammeleht et al, 2022). In the years 2014 to 2016, 2018 and 2023 to March, no studies were entered.…”
Section: Resultsmentioning
confidence: 99%
“…(Antes et al, 2019;Carnero et al, 2017;Davies & Lindvig, 2021;Deniau, 2023;Hyytinen & Löfström, 2017;Knysh et al, 2020;Pizzolato & Dierickx, 2022;Roje et al, 2021;Stigger et al, 2022; Yi et al(Abdi, Fieuws, et al, 2021;Armond & Kakuk, 2022;Bouter et al, 2016;Chua et al, 2022;da Silva et al, 2020;Deniau, 2023;Haven et al, 2019;Hofmann et al, 2020;Hofmann & Holm, 2019;Kalichman, 2020;Malički et al, 2019;Olesen et al, 2019;Simon et al, 2019;Tomić et al, 2022) …”
unclassified